AN ANALYSIS OF GRAMMATICAL ERROR IN THESIS ABSTRACT OF FACULTY OF AGRICULTURE STUDENTS OF BORNEO TARAKAN UNIVERSITY - Luthfiani, Andita (Borneo Journal of English Language Education, 2019)
The aims of this research are: (1) to identify and describe the types of grammatical error in thesis abstract of Agriculture Faculty students of Borneo Tarakan University, and (2) to describe the possible causes of the grammatical error. This research is a descriptive study. 56 abstracts from year 2016 were taken as the samples. Taking the samples was done in the university library and those were in the form of softcopy. To collect the data, researcher followed some steps; they were identifying, categorizing, and describing the error. To categorize the errors, researcher used Surface Structure Taxonomy (SST) and also used Comparative Analysis Taxonomy (CAT) to analyze the causes of errors. The results of this research show that 2832 errors found in 56 abstracts and those were categorized based on the four types of SST. The errors percentages are 22.2% for omission error, 27.7% for addition error, 18.7% for misordering error, and 31.1% for misformation error. Besides, the errors based on the CAT, it was found that developmental error were 1331 errors, interlingual error were 830 errors, ambiguous error were 435 errors, and other error were 146 errors. From the results, the errors mostly found are misordering error and developmental error.